Synthesis of a Bis(NHC)Pd complex via oxidative addition of a C-C bond in a biimidazolium ion - Baker, M.; Brown, David; Hesler, V.; Skelton, B.; White, A. (American Chemical Society, 2007)
The formation of a cyclophane-NHC complex of Pd-(II) Via oxidatiVe addition of a C-C bond in a bridged biimidazolium ion to Pd(0) is described. The actiVe Pd(0) species appears to be [Pd(PPh3)2Br]-. Simple (unbridged) biimidazolium ions do not form NHC complexes under similar conditions.